Sedimentology and mineralogy of surface sediments from the Chilean continental margin - Lamy, Frank; Hebbeln, Dierk; Wefer, Gerold (Supplement to: Lamy, F et al. (1998): Terrigenous sediment supply along the Chilean continental margin: modern regional patterns of texture and composition. Geologische Rundschau, 87(3), 477-494, https://doi.org/10.1007/s005310050223, 1998)
The regional patterns of texture and composition of modern continental slope and pelagic sediments off Chile between 25°S and 43°S reflect the latitudinal segmentation of geological, morphological, and climatic features of the continental hinterland. Grain-size characteristics are controlled by the grain-size of source rocks, the weathering regime, and mode of sediment input (eolian off northern Chile vs fluvial further south). Bulk-mineral assemblages reveal a low grade of maturity. Regional variations are governed by the source-rock composition of the different geological terranes and the relative source-rock contribution of the Coastal Range and Andes, as controlled by the continental hydrology. The relative abundance of clay minerals is also predominantly influenced by the source-rock composition and partly by continental smectite neoformation. Latitudinal variations of illite crystallinities along the Chilean continental slope (and west of the Peru-Chile trench) clearly reflect modifications of the weathering regime which correspond to the strong climatic zonation of Chile.